International teaching practice in technical and vocational education - Amin, Nor Fadila (2015)
Teaching practice is a core component of a bachelor degree in education, and it enables student teachers to acquire initial teaching competencies in the real school setting. This paper presents the perceptions, readiness and challenges of student teachers in the area of technical and vocational education on the international teaching practices program. The study involved 34 undergraduate students who joined a four-week international teaching practice in three provinces of Indonesia namely Central Java, Yogyakarta and South Sulawesi. The questionnaire was used as a research instrument with value of reliability is 0.88. Data was analyzed descriptively and inferentially using the value of frequency, percentage and one-way ANOVA respectively. The findings show that the readiness, challenges and perceptions of student teachers towards the international teaching practice are high. There is no significance difference depicted by respondents from different programs in the three constructs. Based on this study, directions for further research are identified to enhance the implementation of international teaching practice in the future.